Optimize the Role of The State Islamic High School (MAN) Bondowoso Principal in Promoting Digital-Based Learning - Khofi, Mohammad Bilutfikal; Santoso, Santoso (JERIT: Journal of Educational Research and Innovation Technology, 2024)
The principal of the madrasah is expected to be an agent of change, capable of leading the digital transformation process in the madrasah environment. Therefore, optimizing the role of the madrasah principal in promoting digital learning is very important, not only to meet the needs of the times, but also to improve the overall quality of education in the madrasah. This study adopts a qualitative approach. This study aims to identify and understand how the principal of the madrasah in MAN Bondowoso optimizes her role in promoting digital-based learning. Data was collected through observation, documentation and in-depth interviews. Data analysis was conducted using Miles and Huberman's (1994) interactive model, which includes data reduction, data presentation, and drawing conclusions. The principal of the MAN Bondowoso madrasah has been able to optimize his role in supporting the digital transformation of the madrasah. With the role of educator, manager, administrator, supervisor, leader, innovator, and motivator, the principal of the madrasah effectively improves the competency of digital teachers, manages the technology infrastructure, and formulates policies that support digital-based learning. These efforts create a more innovative and adaptive educational environment. The principal has also been able to motivate teachers and students to actively participate in the digitalization process. The overall effort to optimize this role contributes significantly to improving the quality of education and students' readiness to face the challenges of the digital age.